Effect of Calcination Temperature in Preparation of ZnO-SiO2/Laponite and its Physical Character and Photocatalytic Activity - Fatimah, Is (Asian Journal of Chemistry, 2014)
ZnO-SiO2/laponite was prepared by sol-gel preparation procedure consit of SiO2 pillarization to laponite followed by ZnO dispersion by using zinc acetate as precursor. The obtained material was characterized by X-ray diffraction, scanning electron microscopy, energy dispersive spectrometry, diffuse reflectance UV-visible (DRUV-visible) and N2 adsorption-desorption analysis. The photocatalytic performance of the material in decolorization of methylene blue was also investigated. Compared with ZnO-SiO2 nanoparticles, it is concluded that ZnO-SiO2/laponite possess higher photocatalytic activity and influenced by calcination temperature.